1996
DOI: 10.1007/bf02331378
|View full text |Cite
|
Sign up to set email alerts
|

Application of selected cationic dyes for the semiquantitative estimation of glycosaminoglycans in histological sections of articular cartilage by microspectrophotometry

Abstract: Selected commonly used cationic dyes, viz. Thionin, Safranin O, Toluidine Blue O, Dimethylmethylene Blue, Cuprolinic Blue, Cupromeronic Blue, N,N'-Diethylpseudoisocyanine, and a modified PAS-method, and staining methods with a variety of alternative procedures, e.g., variation of pH, use of the critical electrolyte concentration method, and blocking reactions (methylation-saponification, carboxymethylation), were tested to select optimal staining procedures for the semiquantitative histochemical estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 39 publications
0
102
0
Order By: Relevance
“…Recently researchers have been applying cationic dyes, such as Safranin O, for the semiquantitative estimation of the glycosaminoglycans in histological sections of the articulate cartilage for microspectrophotometry [41]. He found an initial increase of proteoglycans (Safranin O), then with a decrease starting after 20 hours duration of load that produced a strong inhibitory effect on the superficial zone.…”
Section: Discussionmentioning
confidence: 99%
“…Recently researchers have been applying cationic dyes, such as Safranin O, for the semiquantitative estimation of the glycosaminoglycans in histological sections of the articulate cartilage for microspectrophotometry [41]. He found an initial increase of proteoglycans (Safranin O), then with a decrease starting after 20 hours duration of load that produced a strong inhibitory effect on the superficial zone.…”
Section: Discussionmentioning
confidence: 99%
“…The GAG content of complex membranes was determined using a colorimetric method based on binding of toluidine blue [20,21]. To assay bound GAG in complex membranes on a 24-well plate, the overlying solution was first aspirated and the membrane rinsed once with PBS.…”
Section: Gag Quantification Assaysmentioning
confidence: 99%
“…Kiviranta et al [Ill and Kiraly et al [9] showed that the proteoglycan content of articular cartilage is inversely proportional to transmission values obtained by this method. The diameter of the measuring aperture was 1 pni at a wavelength of 500 nm.…”
Section: Methodsmentioning
confidence: 99%